Current perspectives on quinazolines with potent biological activities: A review. Issue 10 (19th May 2018) - Gupta, Tanya; Rohilla, Ankit; Pathak, Ankita; Akhtar, Md Jawaid; Haider, Md Rafi; Yar, M. Shahar
ABSTRACT: Quinazoline is a heterocyclic compound having biological activities. It is aromatic in nature having bicyclic structure containing benzene ring and pyrimidine ring. Quinazoline and its derivatives are found to have wide range of biological activities that is anticancer, analgesic, antimicrobial, antihypertensive, anticonvulsant, antimalarial, antitumor, and anti-tubercular activities. The purpose of this review is to highlight the recent researches made by researchers on various biological activities of quinazoline derivatives on different targets. GRAPHICAL ABSTRACT: